Ornamentation of dermal bones of Metoposaurus krasiejowensis and its ecological implications - Antczak, Mateusz (PeerJ, 2018)
BACKGROUND: Amphibians are animals strongly dependent on environmental conditions, like temperature, water accessibility, and the trophic state of the reservoirs. Thus, they can be used in modern palaeoenvironmental analysis, reflecting ecological condition of the biotope. METHODS: To analyse the observed diversity in the temnospondyl Metoposaurus krasiejowensis from Late Triassic deposits in Krasiejów (Opole Voivodeship, Poland), the characteristics of the ornamentation (such as grooves, ridges, tubercules) of 25 clavicles and 13 skulls were observed on macro- and microscales, including the use of a scanning electron microscope for high magnification. The different ornamentation patterns found in these bones have been used for taxonomical and ecological studies of inter- vs. intraspecific variation. RESULTS: Two distinct types of ornamentation (fine, regular and sparse, or coarse, irregular and dense) were found, indicating either taxonomical, ecological, individual, or ontogenetic variation, or sexual dimorphism in M. krasiejowensis. DISCUSSION: Analogies with modern Anura and Urodela, along to previous studies on temnospondyls amphibians and the geology of the Krasiejów site suggest that the differences found are rather intraspecific and may suggest ecological adaptations. Sexual dimorphism and ontogeny cannot be undoubtedly excluded, but ecological variation between populations of different environments or facultative neoteny (paedomorphism) in part of the population (with types of ornamentations being adaptations to a more aquatic or a more terrestrial lifestyle) are the most plausible explanations.